1985
DOI: 10.1104/pp.77.1.64
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chilling Temperatures upon Cell Cultures of Tomato

Abstract: ABSTRACr MATERIALS AND METHODSThe effect of chilling temperatres upon cell cultures of tomato (Lycopersicon eaculektum Mill cv 'VF36,' and cv 'VFNT Cherry,' and L hirsutam Humb. & Bonpl.) was tested. Doubling times for L escuketum were 2 to 3 days at 28°C, and 3 to 8 days at 12°C. No (12,14). L. hirsutum is reported to show greater tolerance to chilling temperatures than the domestic tomato (3, 7, 12-15, 18, 20 (11), 100 LM iron EDTA, 3% sucrose, 2 mg/l 2,4-D, and 0.1 mg/l BA or isopentenyl adenine. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 16 publications
(12 reference statements)
0
8
0
Order By: Relevance
“…Suspension-cultured cells of tomato (Lycopersicon esculentum VF36) were obtained from B. Williams (Plant Cell Research Institute, Dublin, CA) and grown on MS medium as described by that group (7). Cells were adapted to growth on DCB by stepwise transfers in gradual increments on increasing levels of DCB beginning at 1 ,aM DCB.…”
Section: Adaptation and Growth Of Cell Culturesmentioning
confidence: 99%
“…Suspension-cultured cells of tomato (Lycopersicon esculentum VF36) were obtained from B. Williams (Plant Cell Research Institute, Dublin, CA) and grown on MS medium as described by that group (7). Cells were adapted to growth on DCB by stepwise transfers in gradual increments on increasing levels of DCB beginning at 1 ,aM DCB.…”
Section: Adaptation and Growth Of Cell Culturesmentioning
confidence: 99%
“…Damage was severe in the presence of glucose, but was markedly reduced in the presence of mannitol, suggesting that injury was related to enhanced cell division potential of protoplasts in the glucose medium. Studies by Breidenbach and Waring (1) indicated that tomato cell suspensions and seedlings responded comparably when subjected to chilling stress, while DuPont et al (2) found that chilling temperatures inhibited growth, but did not kill tomato cells in suspension culture.…”
mentioning
confidence: 99%
“…Methods were as previously described (6). Callus was initiated from roots (growth curve experiment) or hypocotyls (all other experiments) of aseptic tomato seedlings (Lycopersicon esculentum Mill cv VF36) germinated on agar.…”
Section: Methodsmentioning
confidence: 99%
“…The cultures were maintained in 200 ml of medium in 500 ml flasks on a reciprocating shaker at 28°C. The medium (6) Preparations enriched in sealed vesicles were prepared by centrifugation onto a cushion of 10% 70 kD Dextran (4,18). Growth Curve Experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation